Social networks and decision-making for coastal land-use planning, development and adaptation response. Issue 2 (2nd April 2016) - Clarke, Beverley; Tually, Selina; Scott, Michael
ABSTRACT: Sea-level rise has become a front-and-centre policy and management challenge for governments, planners and coastal managers. Local government coastal adaptation responses to climate change impacts and sea-level rise is critical. The purpose of this paper is to illustrate the powerful role of social networks in the uptake of science in coastal decision-making. A case study is presented from metropolitan Adelaide, South Australia, to examine how an urban coastal development deemed susceptible to coastal hazards was approved. The social network that formed around the proposed development, with its informal connections and shared cultural values, influenced the decision which suited the needs of the network but did not align with provisions in state coastal protection policy. This paper provides an insight into the strategic capability of social networks and the case presented highlights the potential of social network analysis techniques to better understand the complexity of coastal decision-making processes.